Pola Pengembangan SIA Untuk Pemenuhan SDGs: Temuan Dari Rumah Sakit Muhammadiyah - Anna Marina; Sentot Imam Wahjono; Soo Fen Fam (UMSurabaya Publishing, 2016)
The aim of this study is to describe the pattern of development of AIS in the hospital. There are three models of the development of AIS are: Waterfall, Iterative, and Spiral. Hospitals can use AIS package software that has been made and sold in the market but the software package does not allow to be developed in line with business development, organization, and technology. That is why many enterprises that designs and develops its own with the intention of AIS can meet the needs and desires of the company. This research was conducted with qualitative approach. The location of this research is in the hospital owned by Muhammadiyah in Lamongan and Ponorogo, East Java, Indonesia. Data were collected by in-depth interviews, outside observation, and documentation. The key informant involved a total of 56 people, consisting of 40 operators, 10 supervisors, and 6 managers. The data collected will be analyzed using content analysis. The research finding is a pattern of AIS development in accordance with the hospitals. Contributions from these research finding is the possibility of AIS development pattern can be used by other hospitals or other business entities when developing AIS. Keywords : Accounting Information System (AIS), AIS development, hospital, Muhammadiyah Correspondence to :a_m_rina@yahoo.com1,sentot.imamw@fe.um-surabaya.ac.id2, famsoofen@utem.edu.my